Overarching goals: a strategy for improving healthcare quality and safety?. Issue 3 (30th November 2012) - Nanji, Karen C; Ferris, Timothy G; Torchiana, David F; Meyer, Gregg S
Abstract : The management literature reveals that many successful organisations have strategic plans that include a bold 'stretch-goal' to stimulate progress over a ten-to-thirty-year period. A stretch goal is clear, compelling and easily understood. It serves as a unifying focal point for organisational efforts. The ambitiousness of such goals has been emphasised with the phrase Big Hairy Audacious Goal ('BHAG'). President Kennedy's proclamation in 1961 that 'this Nation should commit itself to achieving the goal, before this decade is out, of landing a man on the moon and returning him safely to earth' provides a famous example. This goal energised the US National Aeronautics and Space Administration, and it captured the attention of the American public and resulted in one of the largest accomplishments of any organisation. The goal set by Sony, a small, cash-strapped electronics company in the 1950s, to change the poor image of Japanese products around the world represents a classic BHAG. Few examples of quality goals that conform to the BHAG definition exist in the healthcare literature. However, the concept may provide a useful framework for organisations seeking to transform the quality of care they deliver. This review examines the merits and cautions of setting overarching quality goals to catalyse quality improvement efforts, and assists healthcare organisations with determining whether to adopt these goals.